Analisis Yuridis Fungsional Digital Gerrymandering dalam Kontitusionalitas Pemilu di Indonesia: Relevansi, Manifestasi, dan Justifikasi Hukum - Albertus Drepane Soge; Antonius Maria Laot Kian; Hassan Bin Mussad (Jurnal Bawaslu Provinsi Kepulauan Riau, 2026)
Digitalization has given rise to new threats to the integrity of elections in Indonesia, one of which is Digital Gerrymandering (DG). This study aims to analyze the factual manifestations of DG and its legal accountability in the context of election law and the Personal Data Protection Law (PDP Law). The method used is a normative legal analysis of the principles of LUBER JURDIL, digital campaign regulations, and the accountability of the General Election Commission (KPU) as the Data Controller. The results of the analysis show that DG has been functionally applied in Indonesia, manifested through Political Microtargeting (PMT) and voter data abuse (including SIDALIH leaks). Normatively, this practice is unjustifiable because it violates constitutional election principles, particularly the principles of honesty and fairness, which require an equal playing field. Although the KPU is legally responsible for the failure to protect personal data, the enforcement of substantive (administrative) sanctions is hampered by regulatory gaps—in particular, the fact that a Personal Data Protection Agency (LPDP) has not yet been established and that a Government Regulation on the procedures for imposing sanctions under the PDP Law has not yet been enacted. To address this threat, it is recommended that digital campaign regulations be reformed to include algorithmic transparency and to accelerate the establishment of the LPDP and implementing regulations for the PDP Law.